Comparison of On-Pump and Off-Pump Coronary Artery Bypass Grafting. Our experience of participation in the international study - Gogayeva, O.; Rudenko, A.; Lazoryshynets, V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Aim. To present our experience in the international, multicenter, randomized clinical trial CORONARY (CABG Off or On Pump Revascularization Study) in which on-pump and off-pump CABG was compared. Materials and methods. Eleven patients who signed informed consent and matched at least 1 inclusion criterion according to the CORONARY study protocol were randomized in Institute site. All the patients completed the EuroQol-5D questionnaire and underwent neurocognitive tests (MOCA, DSS, Trial Making test). Results. The mean age of the enrolled patients was 62.9 ± 6.2 years. All the patients (100%) had myocardial infarction (MI) in anamnesis, 4 (36.35%) patients had cerebrovascular disease (CVD), 5 (45.4%) patients had chronic kidney disease (CKD), and 4 (36.35%) had diabetes mellitus (DM). The average number of hemodynamically marked coronary artery stenoses was 2.45 ± 0.78, the left main lesion was diagnosed in 2 (18.18%) cases. The severity of the patients’ condition according to the ES II scale averaged 4.9 ± 1.23%. Five (45.5%) patients underwent on-pump CABG, and offpump CABG was performed in 6 (54.5%) cases. The average on-pump time was 122.8 ± 23.5 minutes; the aortic clamp time was 68.4 ± 9.6 minutes. The average number of grafts was 3.5 ± 0.78. In the postoperative period, paroxysm of atrial fibrillation occurred in 4 (36.35%) patients. One (9.09%) patient had fatal ischemic stroke on day 5 after CABG. The patients were discharged on average within 8.5 ± 2.7 days. According to the study protocol, the condition of patients was monitored annually by telephone; 8 (72.7%) patients completed all visits. In 1 (9.09%) patient with recurrence of angina pectoris in 4 years after CABG we performed repeat CABG. Conclusions. According to the Institute experience of participation in the CORONARY study, there was 1 (9.09%) death due fatal ischemic stroke in the on-pump CABG group. One (9.09%) patient from the off-pump CABG group had repeated CABG. These results of small studies are generating debates in terms of the effectiveness of CABG technique. In multicenter CORONARY trial the rate of mortality, stroke, myocardial infarction, kidney failure, repeated revascularization of myocardium during 5 years of follow-up was similar in on-pump and off-pump CABG patients groups.